Macro and trace elements signature of periodontitis in saliva: A systematic review with quality assessment of ionomics studies. (27th November 2021) - Baima, Giacomo; Iaderosa, Giovanni; Corana, Matteo; Romano, Federica; Citterio, Filippo; Giacomino, Agnese; Berta, Giovanni N.; Aimetti, Mario
Abstract: Objectives: The present systematic review examined the available evidence on distinctive salivary ion profile in periodontitis compared to periodontal health and provided a qualitative assessment of the literature. Background: Macro and trace elements are essential for cellular physiology, and their changes in biological fluids can be revelatory of an underlying pathological status. Methods: Data from relevant studies identified from PubMed, Embase, and Scopus databases were retrieved to answer the following PECO question: "In systemically healthy individuals, are there any differences in any salivary macro or trace element concentration between periodontally healthy subjects (H) and patients with periodontitis (P)?" Quality of included studies was rated using a modified version of the QUADOMICS tool. A consistency analysis was performed to identify significantly discriminant chemical elements. Results: After the screening of 873 titles, 13 studies were included reporting data on 22 different elements. Among them, levels of sodium and potassium were consistently and significantly higher in P compared to H. Conflicting results were found for all the other elements, despite concentration of calcium, copper, and manganese mostly increased in saliva of P. Levels of magnesium were found higher in P than in H in 2 studies but lower in 3. Zinc resulted significantly increased in saliva from H compared to P individuals in 2 studies, but one study reported opposite results. Four studies were considered as high quality, while reporting of operative protocols and statistical analysis was a major limitation for the others. Due to high methodologic heterogeneity, meta‐analysis was not performed. Conclusions: Levels of macro or trace elements were differentially identified in saliva across diverse periodontal conditions, having a major potential for investigation of oral homeostasis and for high‐resolution periodontal diagnosis. Products of inflammatory physiologic cellular impairment, such as sodium and potassium, were the most consistently associated with periodontitis (PROSPERO CRD42021235744).